Comparison of Adrenergic Beta-blocking Drugs in Angina Pectoris. Issue 5767 (17th July 1971) - Sharma, B.; Meeran, M. K.; Galvin, M. C.; Tulpule, A. T.; Whitaker, W.; Taylor, S. H.
Abstract : The symptomatic, electrocardiographic, and haemodynamic effects of two adrenergic beta-blocking drugs, oxprenolol and propranolol, have been compared in equipotent intravenous doses in six patients with uncomplicated angina pectoris during treadmill exercise. The method of comparison included double-blind assessment and analysis with placebo control and randomized serial comparison in each patient. Both drugs produced an equal amelioration in symptoms in most of the patients. This was closely correlated with improvement in the electrocardiographic changes and a significant reduction in the exercising heart rate and systemic arterial pressure. This method of double-blind combined subjective and objective assessment carries distinct advantages in the comparative assessment of drug treatments in angina pectoris.